Baba Ramdev:A Cult Brand in the Making - Pandey, Mrinalini (Indian Journal of Marketing, 2009)
Creating a powerful brand that has innumerable loyal followers is a marketer's dream come true. The benefit of having these legendry Brands have one common unique feature is that they have the capability to transform their customers into brand evangelists. A devoted fan base that are so emotionally connected with the brand that they it becomes a cult or religion for them. In the book "The Power of Cult Branding", Matthew W Ragas and Bolivar J Bueno, the authors have identified seven golden rules which the cult brands seem to follow. This study uses the same rules to explore the possibility of Baba Ramdev creating a cult for him. As of now, we observe that he has been successful in establishing a lasting poignant relationship with his customers, and all his followers are passionate about him and are fanatically following him. The various findings depict the fact that though unproven till date but is definitely not a 'fad' and has the capability of making a 'cult' for himself.